Analisis Pengembangan dan Dampak Wisata Minat Khusus di Indonesia Berdasarkan Lima Kajian Empiris - Devi Karolina (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Special interest tourism in Indonesia has great potential to boost the local economy and environmental conservation, but its development faces obstacles related to human resources, infrastructure, governance, and pressure on ecosystems. This study aims to synthesize findings from five empirical studies examining various forms of special interest tourism, namely whale shark tourism development strategies in Labuan Jambu, marketing mix and visitor behavior in Kali Suci, rafting tourism development in the Citarum and Papualangi rivers, and the impact of snorkeling activities in Karimunjawa. The method used is a cross-study synthesis by examining data collected through interviews, field observations, and visitor questionnaires at each destination. The results show that although each destination has great potential, there are common challenges in strategic planning, limited human resource capacity, and the need for sustainable management. Based on these findings, the development of special interest tourism requires strengthening governance, increasing community capacity, targeted promotional strategies, and the integration of ecotourism principles in destination management. This synthesis provides strategic guidance for managers and policymakers to improve the social, economic, and ecological sustainability of special interest tourist destinations in Indonesia.